Transforming Waste Management Operations to Green Energy Initiatives: Opportunities and Challenges - Wu, Jy Shing; Tseng, H. K.; Ferrell, J. C.; Liu, X. (International Journal of Energy Economics and Policy, 2017)
Emerging challenges for the landfill enterprises include the increasing difficulty in siting and permitting landfills, rising energy costs, and impending reduction in greenhouse gas emissions. A roadmap is presented to overcome these challenges as well as transform landfill operations to green energy initiatives. A feasibility study including financial analysis was performed for electric energy production from the captured landfill gas, solar-electric energy from closed landfill cells, and bioenergy from buffer and idle lands bordering the landfilling areas. While the landfill- and solar-electric energy options are economically viable, the bioenergy option requires due consideration of production capacity and tax credit and incentives. Returns on investment can provide sustainable solid-waste tipping fees, offset funding required for post-closure expenses, and reduce greenhouse gas emissions without direct land-use change. Energy policies for carbon credits and tax incentives are critical elements to sustain the financing of green energy projects for the waste management industry. Keywords: landfill operation, renewable energy, greenhouse gas, environmental economics JEL Classifications: P18, Q53, Q59